A Comparison of the lists and Categorisation of Meditation Practices (KammaṬṬhĀna) in the Visuddhimagga and *Vimuttimagga. Issue 1 (3rd July 2019) - Kim, Kyungrae
ABSTRACT: This article examines the term kammaṭṭhāna discussed in the Visuddhimagga and the Jiĕ tuō dào lùn or * Vimuttimagga . Although these two texts provide similar lists and expositions for the kammaṭṭhāna, the Visuddhimagga also offers different views and criticisms. The first noticeable difference is in the 10 kasiṇa s, which differ in relation to the last two kasiṇa s. Furthermore, the Visuddhimagga systematises its own discussion by simplifying or specifying that of the Jiĕ tuō dào lùn and raises some criticisms of views found in the Jiĕ tuō dào lùn in the process. All of these features imply that the discussion of meditative practice, especially of the kammaṭṭhāna, has been diverse within the Theravāda tradition.